К экологии большого баклана в Донецком Приазовье - Молодан, Г.Н.; Бронсков, А.И.; Мосин, Г.Г. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Data on number increase of the Cormorant and change of its status in Donetsk region at the Sea of Azov coast are presented for the last 6 years. Firstly the Cormorant was rare on passage and common but non-breeding in summer, later it becomes numerous and breeding species. On Krivaya Spit in the Sea of Azov region there were 154 breeding pairs in 2007 and 1800 breeding pairs - already in 2008. Interactions between the Cormorant and the Great Black-headed Gull are considered. The accumulative role of the Cormorant in attraction of the White and Dalmatian Pelicans is noted. Positive influence of strengthening of a protection regime on the increase in numbers of nesting birds on the Krivaya Spit due to foundation of the Regional Landscape Park "Meotida" is discussed.